East Asian transformation : on the political economy of dynamism, governance and crisis - Henderson, J. W. (Jeffrey William), 1947- (Routledge, 2011)
This book brings together benchmark essays in the field of global political economy, covering the key political-economic issues of East Asian development: the relation between the state and markets; the changing nature of economic governance and its relation to inequality; and the rise of China and its international consequences.